Low Risk of Neurological Recurrence while Awaiting Carotid Endarterectomy: Results From a Danish Multicentre Study. (August 2021) - Lawaetz, Martin; Sandholt, Benjamin; Eilersen, Emilie N.; Petersen, Christian; Tørslev, Katrine; Shilenok, Dmitriy; Houlind, Kim C.; Sillesen, Henrik; Shahidi, Saeid; Rathenborg, Lisbet K.; Eiberg, Jonas
Abstract : Objective: The risk of ipsilateral neurological recurrence (NR) was assessed in patients awaiting carotid endarterectomy (CEA) due to symptomatic carotid artery stenosis and whether current national guidelines of performing CEA within 14 days are adequate in present day practice. Methods: This was a retrospective multicentre observational cohort study. Patients scheduled for CEA due to symptomatic carotid artery stenosis in a five year period, 1 January 2014 to 31 December 2018, from four centres were included. Data from the Danish Vascular Registry (www.karbase.dk ), operative managing systems, and electronic medical records were reviewed. Results: In total, 1 125 patients scheduled for CEA were included and 1 095 (97%) underwent the planned surgery. During a median delay from index event to CEA of 11 days (interquartile range 8–16 days), 40 patients (3.6%; 95% confidence interval [CI] 2.5%–5%) experienced a NR. One third were minor strokes ( n = 12, 30%); half were transient ischaemic attacks (TIA) ( n = 22, 55%); and amaurosis fugax accounted for 15% ( n = 6). Twenty-six (2%) CEA procedures was cancelled, of which one was due to a disabling recurrent ischaemic event (aphasia). There were no deaths or major strokes in the waiting time for CEA. Best medical treatment (BMT) with platelet inhibitory or anticoagulation drugs and a statin was initiated in nearly all patients (98%) at first assessment. The overall 30 day risk of a post-operative major event (death or stroke) was (Kaplan–Meier [KM] estimate) 2.7% (95% CI 1.8–3.8), and not significantly correlated with the timing of surgery. Most (69%) occurred within the first three days. One, two, and three year mortality rate for CEA patients was (KM estimate) 4.8%, 7.8%, and 11.5% respectively. Conclusion: In symptomatic carotid artery stenosis patients awaiting CEA, very few NRs occurred within 14 days. Institution of immediate BMT in specialised TIA/stroke units followed by early, but not necessarily urgent, CEA is a reasonable course of action in patients with high grade symptomatic carotid artery stenosis.